How to Improve Indicators on Women’s Economic Empowerment : Guidance Note on Gender-Sensitive Survey Design and Implementation - World Bank (Washington, DC, 2022)
This guidance note provides recommendations on how to operationalize methodological advances for indicators related to women’s economic empowerment in survey design and implementation, focusing on three key dimensions: asset ownership and control, work and employment, and entrepreneurship. It seeks to facilitate the transfer of internationally recommended best practices into country-level, household survey specific advice. Applying the targeted recommendations presented will allow countries to improve their ability to collect meaningful gender statistics that serve as a critical input to designing policies to improve economic opportunities for all.